Knowledge of, beliefs about, and perceived barriers to the use of the emergency contraception pill among women aged 18-51 in Nova Scotia - Whelan AM; Langille DB; White SJK; Asbridge M; Flowerdew G (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objectives: To investigate women in Nova Scotia (NS), Canada with respect to their knowledge of, beliefs about, and perceptions of barriers to accessing emergency contraception pills (ECP).Methods: A random digit dialing approach was used to survey a representative sample of NS women aged 18-51. Analyses described the knowledge, beliefs, and perceived barriers associated with ECP access among participants. Particular focus was given to differences between younger (age 18-31) and older (age 32-51) women.Results: The survey response rate of 49% achieved the desired sample size of 770. Overall, women in NS appeared to be poorly informed about ECP with regards to effectiveness, proper timing of administration, how it works, as well as how to access Plan B®. Younger women (age 18-31) were significantly more likely than older women (age 32-51) to know that ECP does not always prevent pregnancy (p<0.01), that it can be taken more than 12 hours after unprotected intercourse (p<0.01), and that it is available without a prescription in pharmacies (p<0.01). Thirty percent of women agreed that ECP will cause an abortion, with older women (p<0.01) being more likely than younger women to agree. Cost and lack of privacy in pharmacies were identified as potential barriers to access.Conclusions: Lack of knowledge and the perception that ECP causes an abortion may influence a woman's ability to consider ECP as an option should she find herself at risk of an unplanned pregnancy. To address this, efforts should be made to educate women (including older women) about ECP and its availability in pharmacies.